Sustained censorship in TR (2026-03) (Turkey) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Turkey. Data sourced from OONI.
Censorship Incident ID: TR-2026-0124. Severity: critical. Confidence: 72%